Mongolia Country Program Evaluation FY05-13 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2016)
From 2005 to 2013, a mining boom quickly promoted Mongolia from a low-income to a middle-income country. Although the World Bank Group strategy initially overlooked the challenge of the mining boom, the new country management team that came on board in 2005 decided to prioritize mining issues in a more selective framework. This involved taking a set of bold steps to support Bank Group engagement in the extractive industry, including basing for the first time a senior mining specialist in the field and conducting an in-depth political economy analysis. Building on this, the country team was able to design a comprehensive program of outreach to the government, parliament, and civil society to build a consensus on the need for efficient and fiscally sustainable management of earnings from the revenues derived from the mineral boom. The Independent Evaluation Group considers the Bank’s performance to be satisfactory; however, its contribution to outcomes remains moderately satisfactory. The Bank revised its strategy to adopt relevant objectives centered on the mining agenda and designed an overall effective program. The Bank displayed flexibility and innovation in implementing the program and built awareness about environmental issues. As to results on the ground, Bank projects have had a highly satisfactory impact in improving rural livelihoods and reducing herders’ vulnerability. Looking ahead, the Bank Group would need to: (i) build demand and capacity for good governance; (ii) pursue efforts to improve public investment; (iii) strengthen domestic capacity for policy simulation; (iv) assist in the strengthening of the banking system; and (v) support fiscal decentralization. In the interests of selectivity, the Bank could scale back its support for the urban sector.